DETERMINING GENDER AS PERSONAL CHARACTERISTIC THAT INFLUENCE UTILIZATION OF ONLINE LIBRARY SERVICES BY DISTANCE STUDENTS AT THE UNIVERSITY OF NAIROBI, KENYA - Gor, Peter Ochieng; Mbwesa, Prof. K. Joyce; Charles, Prof. Rambo M. (IJRDO- Journal of Educational Research, 2016)
The purpose of this study was to determine factors influencing utilization of online library services by distance students at the University of Nairobi. Specifically the study sought to achieve one objective; to examine how gender as a personal characteristic influence utilization of online library services by distance students at the university of Nairobi. The researcher applied an eclecticism research paradigm. The study adopted descriptive survey design. Data was collected using self-administered questionnaire and interview schedule. The study targeted a total of 1000 students and 14 librarians in the school of continuing and distance education. The sample therefore comprised of 278 distance students and 14 librarians. A pilot study was conducted with 28 student respondents and 1 librarian. This constituted 30% of the study sample. The reliability of the instruments was 0.72. The researcher applied captive audience technique to collect data from the respondents. Data were analysed using frequency counts, the mean and standard deviation and hypothesis was tested using Chi-square, T-test, one way ANOVA and Regression analysis at0.05 level of significance. The key findings revealed that, there was no significant relationship between distance students gender and utilization of online library services at the University of Nairobi. For example, 49.3% of the male respondents considered using online library services daily, twice and once a week compared to 13.6% of the female gender. The findings have important implications in utilization of online library services. For instance, all distance students irrespective of their gender should be encouraged to use online library services provided by the university. A study may be carried out to investigate the effects of personal characteristics and institutional based factors on effective utilization of online library services in private universities. The researcher considered the ethical considerations so as to avoid plagiarism and ensured confidentiality.